Is professionalisation possible within the political culture of Bangladesh - Quddus, S. M. Abdul (2010)
“Profession” and “professionalization” are much-debated sociological concepts and the criteria which distinguish professions from other occupations have been strongly contested. Professionalization is a process of occupational change or development that involves the enhancement of the standard and quality of practice, as well as of the status and level of vocational rewards. It is also mentioned in the western discussions that the dynamics in the professionalization process include: (a) state recognition and the delegation of power; (b) practitioners’ commitment to practicing a body of knowledge and skills of special; (c) specific material rewards so that practitioners have a high degree of; and (d) professional organization as a means of exercising control over recruitment, training, certification and standards of practice. Is this paper we have argued that in addition to the above-mentioned actors and factors, the existing political culture and its inherent dynamics of a given society like Bangladesh also has a strong influence in the professionalization process of occupations